Stress, Gossip, and Cynism; The mediatory role of Abusive Supervisor towards Emotional Exhaustion in the Banking Industry of Pakistan - Raza , Muhammad; Khan, Muhammad Kamran; Quadri, Syed Shameel Ahmed; Khawaja, Wasim Shahid (Pakistan Journal of Humanities and Social Sciences, 2023)
The main objectives of this study are to examine stress, cynicism, and gossip's impact on emotional exhaustion. However abusive supervision is used as a mediator to check the governing role between stress, gossip, and cynicism which cause emotional exhaustion to the employees of the education sector of Pakistan. The research is based on primary data and data collected by questionnaire, Google form survey was used to collect the convenient sampling data of education sector employees working in Pakistan. Smart Pls is utilized to assess measurement and structural models. All Hypothesis was tested and results revealed the association between stress, gossip, and cynicism with the mediating role of abusive supervisor influence on emotional exhaustion. Surprisingly gossip has no impact on emotional exhaustion. This study examines the factors that contribute to emotional exhaustion in subordinates raised as a result of abusive supervision. This has a negative impact on the subordinates' mental health and led to mental and emotional exhaustion. The research significantly proved that the mediating impact of abusive supervision on stress, gossip, and cynicism is related to emotional exhaustion.